1998
DOI: 10.1093/oxfordjournals.ndt.a027844
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of renal failure in idiopathic membranous nephropathy with azathioprine and prednisolone.

Abstract: Oral prednisolone and low-dose azathioprine is an effective therapy for progressing renal failure due to IMN, and induces remission of nephrotic syndrome. Side-effects are less than other immunosuppressive regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Various immunosuppressive agents have been used in the treatment of patients with IMN, including chlorambucil, cyclophosphamide, azathioprine, cyclosporine (CsA), mycophenolate mofetil (MMF), tacrolimus, corticotropin, and, most recently, the anti-CD20 monoclonal antibody rituximab and the anti-C5a monoclonal antibody eculizumab. 3,8,9,14,15,[56][57][58][59][60][61]63,64,66,67,69,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Relevant data from the most important studies are listed in Tables 3 and 4. There are no randomized trials that compared the various classes of agents. It therefore is difficult to draw hard conclusions.…”
Section: Are All Immunosuppressive Agents Equally Effective?mentioning
confidence: 99%
See 1 more Smart Citation
“…Various immunosuppressive agents have been used in the treatment of patients with IMN, including chlorambucil, cyclophosphamide, azathioprine, cyclosporine (CsA), mycophenolate mofetil (MMF), tacrolimus, corticotropin, and, most recently, the anti-CD20 monoclonal antibody rituximab and the anti-C5a monoclonal antibody eculizumab. 3,8,9,14,15,[56][57][58][59][60][61]63,64,66,67,69,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Relevant data from the most important studies are listed in Tables 3 and 4. There are no randomized trials that compared the various classes of agents. It therefore is difficult to draw hard conclusions.…”
Section: Are All Immunosuppressive Agents Equally Effective?mentioning
confidence: 99%
“…72,85 Other studies focused on patients with progressive renal failure and reported more promising results (Table 4). [74][75][76]86 Bone et al 74 evaluated outcome after the start of azathioprine therapy in 21 patients with evidence of progressive renal insufficiency, reflected by a mean decrease in creatinine clearance of 23 mL/min/y. These patients were followed up for 10 years.…”
Section: Are All Immunosuppressive Agents Equally Effective?mentioning
confidence: 99%
“…1,2 Treatment with several immunosuppressive agents has shown beneficial effect on the course of this disease [3][4][5][6][7][8][9][10][11] ; however, controversy persists regarding the proper timing of immunosuppression and the best therapeutic regimen. [12][13][14][15] The appearance of spontaneous remission (SR) in IMN not induced by immunosuppressive therapy is a well known characteristic of the disease.…”
mentioning
confidence: 99%
“…Other trials suggest that aggressive therapy is useful (37, 38). Studies using azathioprine (39, 40), cyclophosphamide (41, 42), and chlorambucil (41, 42) reported favorable results, although 1 study suggested azathioprine did not affect prognosis (40). Several reviews suggested immunosuppressives are useful, especially if high‐grade proteinuria is persistent (43, 44), and two meta‐analyses showed a cumulative beneficial effect for cyclophosphamide and chlorambucil (45, 46).…”
Section: Discussionmentioning
confidence: 99%